IIUM: a successful story of integration of Islamic and human sciences - Ahmad H.Osman, Rahmah (2017)
This paper studies the case of integration of Islamic and Human Sciences in theory and practice by highlighting the achievements of International Islamic University Malaysia (IIUM). This paper follows qualitative descriptive analysis approach. It highlights that IIUM is the pioneering institution in cultivating the idea of integration, and the Kulliyah (Faculty) of Islamic Revealed Knowledge and Human Sciences (KIRKHS) plays a vital role in that process. Integration of knowledge is a process/method/way to generate a comprehensive educational reform for the betterment of humankind. It should not be considered a new phenomenon as Muslims have embraced integration of religious and human sciences throughout Islamic history. The first part of the paper deals with the meaning of integration and its necessity in establishing the Qur’anic worldview for the Muslim Ummah. The second part of the paper discusses the role of the Kulliyah of IRKHS (or KIRKHS) in realizing the idea of integration. It argues that KIRKHS inculcates integration of Islamic and human sciences through training its faculty members and student development, and through curriculum and teaching material design. The last part of the paper states that the KIRKHS has achieved a significant success in its integration journey, which could be replicated by other educational institutions. In conclusion, this study underscores the necessity of integration of knowledge between revealed and modern sciences as a need of the time, as well as a prerequisite for further development of the Ummah, and suggests that integrated minds are capable of contributing to the society and humanity in a better way.